The research on the electrochemical performance of Li2FeSiO4/mgx and Li2FeSiO4/cux. Issue 11 (2nd November 2021) - Li, Ling; Han, Enshan; Pei, Xinbin; Fu, Chunlong; Zhang, Manna
Abstract: Two lithium ions can be reversibly embedded/detached from the structure of Li2 FeSiO4, thus having a high theoretical discharge specific capacity. However, it has the defects of low conductivity and slow lithium ion diffusion rate, which makes it difficult to realize the deintercalation of more than one lithium ion, and its actual discharge specific capacity is lower than the theoretical capacity. This greatly restricts its development into commercial battery cathode materials. In this paper, Li2 FeSiO4 /Mg x and Li2 FeSiO4 /Cu x ( x = 0.01, 0.02, 0.03, 0.05) are synthesized by solid-state method. The electrochemical performance of Li2 FeSiO4 /Mg0.03 and Li2 FeSiO4 /Cu0.02 is the most stable. The initial discharge capacity of Li2 FeSiO4 /Mg0.03 is 147 mAh/g, the capacity retention is 84.2% after 10 cycles under 0.1 C. The initial discharge capacity of Li2 FeSiO4 /Cu0.02 is 140.9 mAh/g. There is only slight agglomeration in Li2 FeSiO4 /Mg0.03 and Li2 FeSiO4 /Cu0.02 from the SEM. The crystal cell volume of Li2 FeSiO4 /Cu0.02 increases slightly, which is conducive to improving the electrochemical performance.